2005
DOI: 10.1007/s00148-003-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain drain or brain gain: A revisit

Abstract: Recent literature has turned to the brain gain effect, instead of the brain drain effect, that emigration may bring to a source country. This paper, however, suggests brain drain remains a likely outcome. Suppose that foreign language skill affects an individual productivity when working abroad. A brain drain may occur when the (exogenously or endogenously determined) probability of immigration is large. We also consider the case that the probability of immigration is determined by a signal, and provide a cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…With no including of fertility choice in the model, Lien and Wang (2005) showed that if migration probability is a function of migration costs then the openness of migration will cause a brain drain for the source country. the short run, an increase in p H would lead to a brain drain, while the reduced average human capital would lead to an increase in both x L t and x H t .…”
Section: Same Probabilities Of Migration For Low-andmentioning
confidence: 99%
See 1 more Smart Citation
“…With no including of fertility choice in the model, Lien and Wang (2005) showed that if migration probability is a function of migration costs then the openness of migration will cause a brain drain for the source country. the short run, an increase in p H would lead to a brain drain, while the reduced average human capital would lead to an increase in both x L t and x H t .…”
Section: Same Probabilities Of Migration For Low-andmentioning
confidence: 99%
“…A static model with migration costs (such as language skills preparation) was developed by Lien and Wang (2005) in which they found that when including such costs, the openness to international migration may well create a brain drain. Since it is quite common for the governments of developing countries to encourage their citizens to migrate to certain foreign countries, the inclusion of the costs of migration allows us to study the impact of these policies.…”
Section: Introductionmentioning
confidence: 99%
“…As the lack of accreditation given to migrant human capital may lead to its waste, we can observe situations where highly skilled migrants are employed in sectors with much lower qualification requirements, in environments where human capital is not being used and therefore depreciating over time. However, some migrants might be willing to experience this kind of brain waste in the short term, as migration is viewed as an investment for the future that will bring further benefits in the long-term period (Jones 1996;Lien & Wang 2005).…”
Section: 'I Know That I Have a University Diploma And I'm Working As mentioning
confidence: 99%
“…the unresolved lInk between mIgratIon and development Appleyard (1992), in his paper entitled "International migration and development: an unresolved relationship" -which has become a key reference on the topic-raised the complexity and difficulty of establishing a causal link between the two phenomena. The existing positive hypothesis in this respectmigration as a factor in development -has been mainly focused on the role of remittances (increasingly more questioned in many contexts), whilst the negative hypothesis-migration as a deterrent for development -has focused largely on the loss of human and intellectual capital (the phenomenon that came to be called the "brain drain"), usually mentioned as the most dramatic consequence of migration for developing countries, although some studies also have relativized this effect (Lien and Wang, 2005).…”
Section: Introductionmentioning
confidence: 99%